Circular RNA Fbxl5 Regulates Cardiomyocyte Apoptosis During Ischemia Reperfusion Injury via Sponging microRNA-146a - Li D; You J; Mao C; Zhou E; Han Z; Zhang J; Zhang T; Wang C (Dove Medical Press, 2022)
Dongjiu Li,1,* Jiayin You,2,* Chengyu Mao,1,* En Zhou,1,* Zhihua Han,1 Junfeng Zhang,1 Tiantian Zhang,1 Changqian Wang1 1Department of Cardiology, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China; 2Department of Emergency, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China*These authors contributed equally to this workCorrespondence: Tiantian Zhang; Changqian Wang, Email ZhangTT2022Dr@163.com; wangcqdr17@163.comObjective: Cardiomyocyte apoptosis critically contributes to ischemia reperfusion injury (IRI), which lacks effective therapeutic strategies. Circular RNAs (circRNAs) serve as novel diagnostic and therapeutic targets in various cardiovascular diseases. CircRNA Fbxl5 is one of the abundantly expressed circRNAs in the heart and its role in myocardial IRI remains elusive.Materials and Methods: Wild-type (WT) mice and neonatal mice ventricular myocytes (NMVMs) were used and subjected to myocardial IRI and anoxia reoxygenation (AR), respectively. Molecular and histological analyses and echocardiography were used to determine the extent of apoptosis, infarct size, and cardiac function.Results: We found that circRNA Fbxl5 was significantly upregulated in the myocardium, as well as in NMVMs subjected to AR. Knockdown of circRNA Fbxl5 ameliorated cardiomyocyte apoptosis, thereby decreasing infarct size and preserving cardiac function. Additionally, in vitro knockdown of circRNA Fbxl5 in NMVMs subjected to AR recapitulated the in vivo findings. Mechanistically, we identified that circRNA Fbxl5 directly sponged and suppressed the endogenous microRNA-146a (miR-146a), thereby weakening its inhibitory effect on MED1, which could further promote the apoptosis of cardiomyocytes.Conclusion: Our findings revealed a novel and critical role for circRNA Fbxl5 in regulating cardiomyocyte apoptosis, and added additional insight into circRNAs mediated during myocardial IRI. The underlying miR-146a-MED1 signaling serves as an important cascade in regulating the apoptosis of cardiomyocytes.Keywords: myocardial ischemia reperfusion injury, circular RNA, microRNA-146a, cardiomyocyte apoptosis